« Plus c’est la même chose, plus ça change » : Réflexions sur les nouvelles dimensions de la crise atlantique - Hassner, Pierre (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1982)
The atlantic crisis is as old as the Alliance itself, but is has now acquired a critical nature in that in affects deeply the relations of the two major countries : The United States and the Federal Republic of Germany.This crisis lies at the crossroads of an evolution in the international context which has stirred up doubts regarding American protection, and of a change in generation which expresses itself in different ways on either side of the Atlantic.The concepts of "comparative vulnerability" and of "mutual fear of decoupling" are used in an attempt to apprise the situation. A study of the search for a German and a European identity and of the Western responses to events in Poland has led the author to make a few recommendations regarding a new policy of the Atlantic Alliance towards Eastern Europe.